EFFECT OF INSTITUTIONAL STRUCTURE ON PERFORMANCE OF NATIONAL GOVERNMENT AFFIRMATIVE ACTION FUNDS IN KENYA - Buyema, Wilfred Muhongo; Rotich, Dr. Gladys Chepkirui; Ombui, Dr. Kepha (European Journal of Business and Strategic Management, 2019)
Purpose: The purpose of this study was to effect of institutional structure on performance of National Government Affirmative Action Funds in Kenya. Methodology: This study adopted a descriptive research design. The study adopted epistemology philosophy. The population of this study comprised of National Affirmative Funds. The target respondents comprised of all the management staff of these institutions whose total number was 195. The study adopted a census design and selected all the 195 managers in all the 6 National Government Affirmative Action Funds in Kenya. Primary data for this study was collected using a questionnaire while secondary data was collected from published reference materials such as reports and journals. Descriptive statistics using the mean and standard deviation and, inferential statistics involving correlation and regression analysis were used to analyze quantitative data. Qualitative data was analyzed through content analysis. Results: ANOVA results indicated that institutional structure has a significant relationship with performance of affirmative funds. The results also showed that institutional structure is a good predictor of performance of affirmative funds. Regression of coefficients results further established that institutional structure has a positive and significant relationship with performance of affirmative funds. Unique Contribution to Theory, Practice and Policy: Based on the study findings, the management was recommended to come up with a board composition policy that states the number of board members, gender constituent, expertise and other diversities such as religion, race and nationality. The policy should also include specifications on board of director's remuneration.